Clinical characteristics and prognostic factors of 70 patients with Sézary syndrome: a single-institutional experience at Moffitt cancer center. Issue 1 (2nd January 2022) - Zhang, Yumeng; Seminario-Vidal, Lucia; Varnadoe, Christa; Lu, Yuanyuan; Dong, Ning; Salamanca, Christopher; Whiddon, Shannen; Bennett, Janice; Hargis, Rebecca; Liu, Hien; Montejo, Michael; Hussaini, Mohammad; et al.
Abstract: Sézary syndrome (SS) is a rare and aggressive leukemic variant of cutaneous T-cell lymphoma, with a median overall survival (OS) rate of 2–4 years. Few studies have described the clinical outcome of SS patients since 2012. We retrospectively analyzed 70 patients diagnosed with SS treated at a high-volume tertiary cancer center between 2000 and 2018. Overall survival at 1 and 5 years was 84.1% and 50.7%, respectively. Univariate analyses identified older age (>65 years) and male sex as poor prognostic factors. Five patients presented with circulating large granular lymphocytic proliferation and had a favorable prognosis. Targeted therapies were effective in treating refractory/relapsed SS patients with a durable response. Therapeutic advancements and the comprehensive treatments used in a multidisciplinary clinic improved OS rates.